Pancasila Sebagai Landasan Demokrasi dan Ham Perspektif Yusril Ihza Mahendra - Dhamar Ibrahim Kadista Putra; Sorayya Febby Kalkautsari; Moh. Faizin; Adhisti Muthia Syawali (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
Pancasila, as the foundational ideology of Indonesia, plays a fundamental role in shaping a democratic system and ensuring the protection of human rights based on justice. From Yusril Ihza Mahendra’s perspective, Pancasila is not merely a normative ideology but serves as a political and legal paradigm that integrates the values of divinity, humanity, unity, democracy, and social justice into the practice of governance. According to Yusril, Indonesian democracy cannot be equated with Western liberalism, which emphasizes individual freedom; rather, it is a constitutional democracy grounded in the moral and spiritual foundations of Pancasila. The values of Pancasila position human rights in a balanced relationship between rights and responsibilities, as well as between individual and collective interests of the nation. Thus, democracy and human rights, in Yusril’s view, are integralistic—citizens’ freedoms are directed toward realizing social j  ustice and order in national life. This article aims to examine Yusril Ihza Mahendra’s thoughts on the relationship between Pancasila, democracy, and human rights, and their relevance within the context of Indonesia’s contemporary constitutional system.